The Effect of Feeding Formula in Honey Bees (Apis mellifera) Using Flow Hive Technology on Honey Production and Quality at PT Kembang Joyo Sriwijaya - Fanisa, Aulia Fahnaz; Dedi Fardiaz; Dewi Masyithoh (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
Bee feeding has long been known and applied in honey bee farming. One way of feeding bees is to give sugar syrup mixed with water. This study aims to determine the effect of supplementary feeding on bees that have been formulated on the production and quality of honey produced. This study also applies one of the artificial hive technologies, namely flow hive. This study also observed how the adaptation of bees and the added value of the flow hive using Apis mellifera honey bees which is known for its high production rate and high adaptability. This research was conducted from September to December 2023 at PT Kembang Joyo Sriwijaya, Malang Regency. The experiment was conducted using 3 flow hives with the same feed formula.  The study showed good feed consumption in stup 1 and decreased feed consumption in stup 2 and stup 3. Honey obtained in stup 1 was 1.5 kg from 1 flow frame. Laboratory test results showed pH levels of 3.4, moisture content of 18.2 %, reducing sugar levels of 55.44 % and 56.71 % and diastase enzyme activity of 3.18 DN and 3.19 DN. In conclusion that formula feeding did not show high honey production when compared to the time taken to reach harvest and also did not show fulfilling reducing sugar content and diastase enzyme activity test results.